Opportunities for Financial Inclusion of Islamic banking in the City of Bima, West Nusa Tenggara - Dwi Aulia Aulia; Dr. Unggul Priyadi S.E., M.Si Unggul Priyadi (ITB AAS INDONESIA Surakarta, 2023)
The development of Islamic banking is increasingly recognized and plays a major role in the economy of the Indonesian people, especially the Muslim community. Even so, there is still a public perception that considers Islamic banking to be the same as conventional banking and considers it easy to access conventional banks in Islamic banking, this shows that Islamic banking financial literacy and inclusion of Islamic banking is still minimal among the public. This study aims to analyze the Opportunities for Financial Inclusion of Islamic Banking in the City of Bima, West Nusa Tenggara Province. The data collection method uses a non-probability sampling technique using a questionnaire. This study used the method of binary logistic regression analysis with the variables used namely gender, age, education and type of work of the respondents. The results show that there is a significant partial effect of the age variable of 0.02, the type of work variable is sig. 0.01, the education variable is 0.05, while gender does not significantly influence the opportunities for Islamic banking financial inclusion with a sig value of 0.347. Effective outreach needs to be emphasized on the introduction of the advantages of Islamic banking in addition to the products and services they have. This is in order to overcome doubts among the public and to increase public confidence in Islamic banking, it is necessary to increase the number of accesses to Islamic banking services. Keywords: Islamic Banking, Financial Literacy, Financial Inclusion Syariah banking.